Sero-prevalence of brucellosis among slaughterhouse workers in Bahr el Ghazal region, South Sudan - Nuol Aywel Madut; Moses Ocan; Adrian Muwonge; John Bwalya Muma; George William Nasinyama; Jacques Godfroid; Ambrose Samuel Jubara; Clovice Kankya (BMC Infectious Diseases, 2019)
Abstract Background Brucellosis is an infectious zoonotic disease and is common especially among pastoral communities in most low and middle-income countries. The aim of this study was to determine sero-prevalence, and risk factors of Brucella infection among Slaughterhouse workers, in Bahr el Ghazal region, South Sudan. Methods A cross sectional study was conducted among Slaughterhouse workers in Bahr el Ghazal region, South Sudan from December 2015 to May 2016. A pre-tested questionnaire was used in data collection. Each randomly selected participant was interviewed and a venous blood sample collected. The blood samples were screened for Brucellosis infection using Rose Bengal Plate Test (RBPT) and confirmed using Competitive Enzyme link Immuno Sorbet Assay (c-ELISA). Data was analyzed using Stata version 13 at 95% level of confidence. Results A total of 234 Slaughterhouse workers were screen for Brucella infection. Overall, a third, 32.1% (75/234) of the participants were sero-positive for brucellosis. The prevalence of brucellosis was higher, 17.1% (40/234) in Wau state compared to other states. There was high prevalence among males, 28.6% (67/234) compared to females 3.4% (8/234). The mean age of study participants was 34.4 ± 9.6 years. A high proportion, 12.8% (30/234) of participants with confirmed brucellosis infection were 31–40 years of age. Brucellosis prevalence was high among butchers, 14.5% (34/234), and meat handlers, 9.0% (21/234). Conclusions Brucellosis is common among animal slaughterhouse workers in Bahr el Ghazal region, South Sudan. There is need for public awareness campaigns and educational programs to help sensitize communities on Brucella infection.